Development and application of a numerical dynamic model for pesticide residues in apple orchards. Issue 6 (28th April 2022) - An, Quanshun; Wu, Yangliu; Li, Dong; Hao, Xianghong; Pan, Canping; Rein, Arno
Abstract: BACKGROUND: Limited understanding of the fate of pesticides in apple orchards may lead to recurring pests or pose risks to food safety. In this study, through a field experiment conducted in an apple orchard, a dynamic plant uptake model, coupled with a soil water model, was developed to simulate measured pesticide concentrations in soil and different plant compartments. RESULTS: Results showed that the overall model could adequately describe the data set of four pesticides in the apple orchard. An estimated 15%–24.7% of applied pesticides were deposited on leaves and 0.37%–0.58% on fruits. Decreasing pesticide concentrations in fruits were observed after pesticide application, with 9.6%–64.8% of this decrease explained by biodegradation, 29.8%–75.8% by fruit growth dilution and 11.3%–47.6% by wash‐off. Furthermore, a first estimation of dietary risks indicated that ingestion of the apples may not represent an acute or chronic risk to human health. CONCLUSION: The dynamic plant uptake model, coupled with the tipping buckets soil water model, could successfully be fitted to describe to the data set for the fate of four pesticides applied in an apple orchard. The contribution of different pathways to pesticide concentration was highly influenced by precipitation, fruit growth dilution and the characteristics of different pesticides. This model can improve our understanding of pesticide fate in apple orchards and has great potential for supporting food safety assessment and decision‐making to minimize impacts arising from pesticide applications. © 2022 Society of Chemical Industry. Abstract : The numerical model could adequately describe the dynamics of pesticide residues in apple orchards and has potential to support dietary risk assessment and decision‐making.